Влијанието на царинската политика врз македонските надворешнотрговски перформанси - Ветеровски, Златко (Економски факултет, УКИМ, Скопје, 2015)
Economic prosperity and national wealth creation is heavily influenced by international trade and customs policy as part of the foreign trade policy. Customs administration has a vital role in regard of the performance of international trade, because it processes all the cross-border movement of goods in order to ensure compliance with the provisions of national law and international trade rules. The costs of foreign trade are of great importance. They have a huge impact on the foreign trade of a country because they can influence the choice of the decision who is going to trade and with whom the trade should be effectuated. These costs also affect the choice in which country the specific products should be produced and what kind of products are offered to the final consumers and they also affect products’ prices. The Republic of Macedonia as a developing and a landlocked country faces a serious challenge in terms of reforming the customs policy and its impact on foreign trade operations, in order to achieve the ultimate goal - greater integration into the global system of international trade of goods and active participation in the global supply chains. Besides the reform of the customs legislation and its adjustment to the customs system of the European Union, the Republic of Macedonia needs to make reforms in the role and organization of the Customs Administration. The future of the customs operations in the Republic of Macedonia should be based on the overall use of electronic and paperless customs procedures. This should lead not only to improvement of the customs operations, but shall also significantly contribute to reducing the costs of implementation of customs procedures. It should be stressed that electronic customs procedures along with other customs systems can not exist in a vacuum. They are the main issues associated to political will, leadership, customs legislation, the necessary human resources and finances.
The impact of the customs policy on the macedonian foreign trade performance
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Ирена Кикеркова.
Keywords: customs policy, customs administration, simplified customs procedures, ecustoms, costs, foreign trade